To Study the Effect of ‘Live’ Miraculous Demonstrations on Increasing Interest in Chemical Sciences - Ghoderao, Sudesh Bhaskar (SCHOOL SCIENCE, 2017)
Chemistry educators are familiar with traditional demonstrations, with which concepts in chemistry are made simpler. By doing ‘live’ miraculous demonstrations, concepts like exothermic reactions generally leading to combustion and the principle underlying of titrations involving colour change are made easy and understandable. The ‘live’ miraculous demonstrations are used to develop interest in students’ about chemical sciences, explanation of so called miracle and to develop scientific temper. The ‘live’ miraculous demonstrations can be done safely with prior training and knowledge. Many students do not favour chemistry because of lack of interest in the subject. So there is a need to develop interest in it. A large number of people believed in various types of so called miracles because of lack of scientific knowledge, attitude and scientific temper. Many godmen, quacks and conmen with similar motive of exploiting and harming mentally, physically and financially the superstitious people in society perform so called miracles. Therefore, there is a need of explaining the scientific knowledge of so called miracles, through students. In the present study ‘live’ demonstrations of so called miracles and booklet prepared about it, is used at undergraduate level as an educational tool. The sample of the study was students studying in SYBSc class in the University of Pune jurisdiction area. The feedback of students through pre- and post-questionnaires was analysed and showed that (i) miraculous demonstrations are favoured by students as an attempt to increase interest in chemistry, (ii) students have an urge to know the chemical science behind the so called miracle, (iii) miraculous demonstrations are exciting and surprising, and (iv) miraculous demonstrations should be incorporated in chemistry curriculum.